A functional 5HT2A receptor polymorphism (His452Tyr) and memory performances in Alzheimer's disease. (2nd June 2016) - Guglielmi, V.; Bizzarro, A.; Valenza, A.; Lauria, A.; Tiziano, F.D.; Lomastro, R.; Masullo, C.
Abstract : The functional His452Tyr polymorphism in the 5HT2A receptor has been described to be associated with verbal memory in healthy adults, with worse episodic memory performances in Tyr452 (T) carriers. The aim of our study was to investigate a possible effect of this polymorphism on memory performances in Alzheimer disease (AD). We enrolled 169 patients affected by probable AD. 5HT2A genotype was determined as previously described. According to their genotype, patients were divided in T carriers (  n = 111) and non-carriers (  n = 69). We evaluated the possible effect of 5HT2A polymorphism on verbal memory tasks. A one-way MANOVA analysis did not show a positive interaction between the two groups (  p > 0.05) at the baseline and at the follow-up. Nevertheless, the analyses of the single-task effect showed lower performances for non-T carriers only in Rey's recognition task. Recent data reported poorer memory performances in healthy subjects carrying the T variant, in age-dependent manner (no differences between T vs. nT carriers were observed for age >50 years). In our AD sample, we did not find significant differences in verbal memory scores in T vs. nT carriers while a significant difference was found only in attentional task. At variance with that in healthy subjects, no correlation has been found between memory profiles of AD patients and His452Tyr polymorphism.